Design and analysis of LDPC codes for joint source-channel decoding of two correlated sensors - Khas, Mohamad; Saeedi, Hamid; Asvadi, Reza (IET communications, 2018)
This study is concerned with the design of ensembles of systematic low-density parity-check (LDPC) codes to increase the lifetime of wireless sensors by taking advantage of the inherent correlation between the transmitted data of the sensors. The authors consider two correlated sensors where the data is encoded independently at each sensor through a systematic LDPC encoder and sent over two independent channels. At the receiver, a joint source-channel decoder consisting of two component LDPC decoders is considered where the encoded bits at the output of each component decoder are used as the a priori information at the other decoder. The authors first perform asymptotic performance analysis using the concept of extrinsic information transfer (EXIT) charts. Then, the developed modified EXIT charts are used to design ensembles for different values of correlation. Our results show that as the average check node degree of the designed ensembles grow, the decoding thresholds corresponding to the designed ensembles approach the theoretical limit. Finite block-length performance evaluation indicates that for larger values of correlation, deploying the designed ensembles through the joint decoder can almost double the sensor's lifetime without increasing the complexity of the encoder.